Seasonal Variability in The Genus-Family Structure of Free-Living Nematode Communities in Organic Shrimp Farming Ponds, Ca Mau Province - Tran, Thanh Thai (H. : ĐHQGHN, 2019)
This study determined the seasonal variability of free-living nematode communities structure (genus/family level) in organic shrimp farms ponds in Tam Giang commune, Nam Can district, Ca Mau province. Based on the result of SIMPER analysis, the average similarity in nematode communities at genus level was low with 30.75% and 30.81% (in dry and rainy season, respectively). However, the average dissimilarity between seasons was considerably high with 71.75%. Terschellingia, Daptonema, and Parodontophora were main genera contributing to similarity/dissimilarity between seasons. At the family level, results of SIMPER analysis showed that the average similarity was low with 37.12% and 39.02% (dry and rainy, respectively). Additionally, the average dissimilarity between dry and rainy season was reasonably high with 64.06%. Specifically, four families such as Linhomoeidae, Xyalidae, Axonolaimidae, and Chromadoridae were the main families contributing to similarity/dissimilarity between seasons. Differences in sediment environmental characteristics between dry and rainy season are the reason for dissimilarity in the nematode communities structure. The high abundance of genus Terschellingia, Daptonema, Parodontophora may be indicative of organic enrichment conditions in shrimp pond sediment in both seasons. Nematodes with their rapid adaptation to changing environments can be used as a potential tool for bio-indicator